Billionaire's island temptation - Stewart, Rachael (Stewart, Rachael. Billionaires for the Rose sisters, 2023)
"A summer fling-- or something more? Jessie Rose is shocked by the instant chemistry she feels when she meets billionaire Joel in Mustique. She's come looking for an escape, and brooding Joel is very clear he's not looking for anything permanent. But letting their guards down while exploring the island together, they can't deny their fling is dangerously close to being a temptation they may not be able to walk away from--"--